An Analysis of Code Switching in Teaching Learning Process at SMPN 2 Manggeng - Riza Purma; Meristika Moetia (Universitas Dehasen Bengkulu, 2023)
This study aim to determine the use of code-switching by teacher in teaching and learning process. This research is qualitative research with the aim of collecting, processing, analyzing, and presenting data objectively about the occurrence of code-switching events carried out by teachers and students in a class located at SMPN 2 Manggeng, Aceh Barat Daya.There are 5 English teachers at the school, but the samples only 3 English teachers.The results of this study indicate that there are three types of code-switching used by teachers, namely tag-switching, inter-sentential switching, and intra-sentential switching according to the opinion of Poplack (2004). From the result of interviews, the teacher revealed that the reason of using code-switching when teaching was due to students'' lack of mastery of English, which made the teaching and learning process not as efficient. Futhermore the teacher believes that the use of code-switching can also increase students' vocabulary, and their English pronunciations.